(untitled) (Research, Society and Development, 2021)
Objective: to propose normative standards for the classification of CA through the performance in the intermittent Yo-Yo test level 1 (Yo-Yo) in children from 5 to 10 years old. Materials and methods: the study consisted of 1,060 children of both sexes. Anthropometric evaluation was performed for characterization and the Yo-Yo was used to assess CA. Results: girls had higher body mass (p <0.005) and lower WC compared to boys (p <0.001), coatis values based on Yo-Yo performance were distributed in low, moderate, high and very high. Conclusion: the present study presented a proposal for reference values for CA, the use of the values proposed by this study, can be a fundamental instrument in the process of evaluating CA in children by health professionals and teachers.